(untitled) (Journal of Parents and Teachers, 2014)
The year 2000 is known as the international year of mathematics, which is why readers are encouraged to research and find useful elements for the classroom. For example, on Manuel Nando’s website you can find many notes and exercises for university entrance exams. Other websites that appear are "Curso de Matemáticas", "El paraíso de las matemáticas" or that of the Real Sociedad Matemática Española.